Emerging Molecular Biomarkers for Early Detection of Antimicrobial Resistance in Clinical Pathogens: A Diagnostic Laboratory-Based Study - Abuong, Fahad Sami; Fallatah, Majed Hashem; Aljuhani, Maryam Awad; Alhirbish, Hanan ahmed; terkustani, wejdan mohammed; Alahmadi, Nouf Oqla; Alsubhi, Razan Faleh; Shamlan, Sara Ali; Aqeeli, Amal Mohammed; Rasheed, Sarah Ayman; et al. (Journal of Posthumanism, 2023)
Background: The global rise of antimicrobial resistance is a serious threat to public health. Conventional culture-based AST is time-consuming, taking 48-72 hours, thus delaying the start of appropriate therapy. The performance of a multiplex molecular panel targeting emerging AMR biomarkers for the rapid detection of resistance in Gram-negative and Gram-positive bacterial pathogens was evaluated directly from clinical specimens and positive blood cultures. Methods: Over a period of 12 months, we typed 1,250 clinical specimens (750 blood cultures and 500 respiratory samples) for the presence of resistance genes by an in-house multiplex PCR coupled to a microarray-based detection system. The panel targeted major resistance markers: blaKPC, blaNDM, blaOXA-48-like (carbapenemases), *mcr-1* (colistin resistance), mecA (methicillin resistance), and vanA/vanB (vancomycin resistance). Results were compared with standard phenotypic AST (VITEK 2 and broth microdilution) as the reference standard. Results: The molecular assay had an overall sensitivity of 98.2% and a specificity of 99.5% compared to phenotypic AST. The median TAT for reporting by molecular assay post-receipt of specimen was 4.5 hours as compared to 48 hours for conventional AST. It correctly identified 45 carbapenemase producers, 120 MRSA isolates, and 15 VRE isolates that were further confirmed phenotypically. It also detected the *mcr-1* gene in two E. coli isolates from blood cultures that showed high colistin MICs on confirmation. Conclusion: Molecular detection of AMR biomarkers allows for the early identification of resistant pathogens with a high degree of speed and accuracy. Implementation of these assays within diagnostic laboratories is critical to markedly reduce the time to effective therapy, to assist infection control practices, and ultimately to improve patient outcomes in the setting of the increasing crisis due to AMR